2012
DOI: 10.1007/s11739-012-0843-4
|View full text |Cite
|
Sign up to set email alerts
|

Preventability analysis of adverse drug reactions detected in two internal medicine departments in Romania

Abstract: In order to improve patient safety, systematic analysis of common and repetitive patterns of preventable adverse drug reactions (pADRs) in the clinical setting should be performed regularly in order to propose adequate prevention strategies. Our aim is to evaluate the preventability of all ADRs collected in a drug information research center database, by spontaneous reporting and clinical surveillance in two internal medicine departments. One reviewer systematically reevaluated all the cases stored in the data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
2
4
1
Order By: Relevance
“…However, the data from a study showed lower preventability for ADRs (12%) compared with our finding (Dequito et al, 2011). As described in previous studies, insufficient monitoring, inappropriate dosing, and DDIs were the most frequent factors involved in ADR preventability (Farcas et al, 2014;Al Damen and Basheti, 2019). Incriminated drugs were withdrawn in 94.29% of the reports, which is in line with a previous study in a psychiatric department of a tertiary care teaching hospital in India (Patel et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, the data from a study showed lower preventability for ADRs (12%) compared with our finding (Dequito et al, 2011). As described in previous studies, insufficient monitoring, inappropriate dosing, and DDIs were the most frequent factors involved in ADR preventability (Farcas et al, 2014;Al Damen and Basheti, 2019). Incriminated drugs were withdrawn in 94.29% of the reports, which is in line with a previous study in a psychiatric department of a tertiary care teaching hospital in India (Patel et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Severe ADRs, as major concerns for public health, are a contributing factor of hospitalizations and morbidity (Rottenkolber et al, 2011;Marques et al, 2014). The analysis indicated a preventability rate of 53.97% among ADRs, comparable with the results of studies conducted in Romania and Jordan showing that 41% and 44.7% of ADRs were preventable, respectively (Farcas et al, 2014;Al Damen and Basheti, 2019). However, the data from a study showed lower preventability for ADRs (12%) compared with our finding (Dequito et al, 2011).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The focus in nine (11%) of the studies was on paediatric care units, with three of these studies being situated in neonatal intensive care units [42][43][44]. Seven (9%) studies involved elderly patient care units, six of which were specialised care units for geriatric patients aged above 65 years [35,[45][46][47][48][49].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Drug-drug interactions (DDIs) with serious adverse consequences for patients at intensive care unit (ICU) occur with high prevalence of 5.3% and are responsible for almost 15.5% of all adverse drug reactions in that patient population (1). In principle, DDIs are all preventable if potential for their occurrence is noticed on time (2). There are numerous softwares providing for rapid, bed-side discovery of clinically relevant potential DDIs, which were already validated in practice, and demonstrated significant sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%